História da química no ensino fundamental I: indicadores de alfabetização científica - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Assuming that the teaching and learning of science aimed at scientific literacy in the Initial Grades, should consider the child as an active participant, that the present investigation entitled, History of Chemistry in Elementary School I: Scientific Literacy Indicators, sought for articulations theoretical and practical, with the objective of investigating the application of the methodology, Inverse Didactic Proposal (PDI), from the contributions of the balance instrument to the History of Chemistry, in a class of the 1st year of Elementary School I. The didactic proposal developed was composed of 10 activities, having the child as the central axis, according to the ideas defended in the theoretical field of the Sociology of Childhood, seeking to answer the research question: How a didactic proposal structured from the history of the balance in Chemistry contributes for scientific literacy in the 1st year of elementary school? For this purpose, we used a qualitative methodology, data collection procedure, participant observation, data collection instruments, oral and graphic language and focused interview, analysis procedures, we used Discursive Textual Analysis (DTA). The initial categories of analysis emerged through the structuring axes of scientific literacy Sasseron and Carvalho (2008). In Category (C1) Basic understanding of fundamental scientific terms, knowledge and concepts, we obtained as a result that children are able to organize, classify, series and test hypotheses and express this through verbal and graphic language according to their age group , with the teacher being responsible for making the necessary adaptations between scientific and school knowledge, taking advantage of the experiences and interactions between children. Through the category (C2) Understanding the nature of science and the ethical and political factors that surround its practice, we found a promising path for the beginning of scientific literacy in the Initial Series, from the History of Chemistry, enabling children to build knowledge scientific studies through the History of Science, giving new meaning to learning, encouraging students to raise and test hypotheses. Finally, the category (C3) Understanding the existing relationships between science, technology, society and the environment, we found that methodologies that seek to make articulations of everyday situations serve as a bridge to scientific literacy and that in this process, the exchanges established between the speeches of children are rich. Based on the results obtained, we consider that the Inverse Didactic Proposal (IDP) can be a methodology used in the scientific literacy process, which can be applied totally or partially. In this sense, the contributions of this research to Science Teaching are diverse, considering that we propose a didactic methodology, which considers children in the teaching and learning process of science, valuing their speeches and graphic productions, understanding that from this construction the children express their worldview, managing to look at science critically.
History of chemistry in elementary education I: scientific literacy indicators
Keywords: Ciências (Ensino fundamental) - Estudo e ensino; Química (Ensino fundamental) - História; CIENCIAS EXATAS E DA TERRA; Letramento científico; História da balança na química; Sociologia da infância; Séries iniciais; Indicadores de alfabetização científica